Exoduses and portraits... or the educational viewpoint made valueable in order to give - Romero Izarra, Gonzalo (Pulso. Revista de educación, 2001)
This article aims to explore the recent exhibition "Exodos" by Brazilian photographer Sebastiao Salgado at the Circulo de Bellas Artes in Madrid from an educational and anthropological perspective. The collection of photographs is not only for looking at, but also observes and asks us questions. Some of these questions are presented in this work. Additionally, the author provides answers and insights gained from the exhibition. The author emphasises the importance of the concerns raised by the exhibition, particularly for those pursuing a career in Social Education, and sheds light on the “behind-the-scenes” aspects of Salgado’s extensive photographic display.